2020
DOI: 10.1055/a-1067-4326
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral endoscopic stenting in patients with unresectable malignant hilar obstruction: a systematic review and meta-analysis

Abstract: Background and study aims Endoscopic stent placement is used for palliative management of unresectable malignant hilar obstruction, which could be achieved by either unilateral or bilateral stent insertion. Materials and methods A literature search was performed to identify studies that reported outcomes of metallic biliary stent placement in patients with malignant hilar obstruction. Weighted pooled rates (WPR) along with 95 % confidence intervals (95 %CI) were calculated to determine and compare ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
(62 reference statements)
0
26
0
1
Order By: Relevance
“…Several studies have investigated unilateral (left or the right duct system) or bilateral stenting. De Palma et al [78] in their RCT of 157 patients with hilar obstruction, comparing unilateral and bilateral stenting, demonstrated superior stent insertion rates with unilateral stenting (88.6% vs. 76.9%, P = 0.04) and higher complication rates with bilateral stenting (26.9% vs. 18.9%, P = 0.03) on intention-to-treat analysis. A meta-analysis by Aghaie Meybodi et al [79] of 1300 patients with hilar strictures demonstrated comparable efficacy and safety for unilateral and bilateral stenting.…”
Section: Type Of Semsmentioning
confidence: 96%
“…Several studies have investigated unilateral (left or the right duct system) or bilateral stenting. De Palma et al [78] in their RCT of 157 patients with hilar obstruction, comparing unilateral and bilateral stenting, demonstrated superior stent insertion rates with unilateral stenting (88.6% vs. 76.9%, P = 0.04) and higher complication rates with bilateral stenting (26.9% vs. 18.9%, P = 0.03) on intention-to-treat analysis. A meta-analysis by Aghaie Meybodi et al [79] of 1300 patients with hilar strictures demonstrated comparable efficacy and safety for unilateral and bilateral stenting.…”
Section: Type Of Semsmentioning
confidence: 96%
“…Several studies investigated whether the biliary drainage should be unilateral or bilateral [ 68 , 69 , 70 ]. On one hand, the unilateral drainage raises the issue of insufficient jaundice relief and risk of infective complications occurrence, on the other hand, bilateral stenting is burden by a higher technical complexity.…”
Section: Complete Versus Incomplete Drainagementioning
confidence: 99%
“…In a multicenter, prospective, randomized study unilateral and bilateral endoscopic drainage showed similar results in terms of success rate, but unilateral stenting was associated with a higher risk for reintervention and shorter patency time [ 71 ]. In a recent meta-analysis of 21 studies involving 1292 patients with malignant HBO, Meybodi M. et al reported that the technical success and the functional success rate were higher in unilateral drainage when compared with the bilateral [ 70 ]. Short-term and long-term complication rates were comparable in the two groups [ 70 ].…”
Section: Complete Versus Incomplete Drainagementioning
confidence: 99%
See 1 more Smart Citation
“…Technical success was significantly higher in the unilateral group compared to the bilateral group (97% vs. 89%; P=0.003). Clinical success rate (98% vs. 94%; P=0.48) and complications were comparable between the 2 groups [ 47 ]. In a retrospective study by Naitoh et al , comparison of endoscopic unilateral and bilateral biliary metal stenting was performed in patients with MHS [ 42 ].…”
Section: Unilateral Vs Bilateral Stentingmentioning
confidence: 99%